Perceptions of patients with early stage breast cancer toward research biopsies. Issue 8 (15th December 2020) - Seah, Davinia S.; Leone, Jose Pablo; Openshaw, Thomas H.; Scott, Sarah M.; Tayob, Nabihah; Hu, Jiani; Lederman, Ruth I.; Frank, Elizabeth S.; Sohl, Jessica J.; Stadler, Zsofia K.; Erick, Timothy K.; Silverman, Stuart G.; et al.
Abstract : Background: The objective of this study was to describe the perspective of patients with early breast cancer toward research biopsies. The authors hypothesized that more patients at academic sites than at community‐based sites would be willing to consider these procedures. Methods: In total, 198 patients with early stage breast cancer were recruited from 3 academic centers (n = 102) and from 1 community oncology practice (n = 96). The primary objective was to compare the proportion of patients willing to consider donating excess tissue biospecimens from surgery, from a clinically indicated breast biopsy, or from a research purposes‐only biopsy (RPOB) between practice types. Results: Most patients (93% at academic sites, 94% at the community oncology site) said they would consider donating excess tissue from surgery for research. One‐half of patients from academic or community sites would consider donating tissue from a clinically indicated breast biopsy. On univariate analysis, significantly fewer patients from academic sites would consider an RPOB (22% at academic sites, 42% at the community site; P = .003); however, this difference was no longer significant on multivariate analysis ( P = .96). Longer transportation times and unfavorable prior experiences were associated with less willingness to consider an RPOB on multivariate analysis. Significantly fewer patients from academic sites (14%) than from the community site (35%) would consider a research biopsy in a clinical trial ( P = .04). Contributing to scientific knowledge, return of results, and a personal request by their physician were the strongest factors influencing patients' willingness to undergo research biopsies. Conclusions: The current results rejected the hypothesis that more patients with early breast cancer at academic sites would be willing to donate tissue biospecimens for research compared with those at community oncology sites. These findings identify modifiable factors to consider in biobanking studies and clinical trials. Abstract : In this study of the willingness of patients with early stage breast cancer to consider biospecimen collection procedures for the purposes of research, most patients were willing to provide blood samples for research but were less likely to consider percutaneous breast biopsies. Longer travel time to the clinic and adverse experiences with prior biopsies, but not treatment center type (academic versus community‐based center), were associated with less willingness to consider research biopsies.